Concurrent Arthroscopic Revision of the Hip Labral and Anterior Capsular Reconstruction Utilizing Iliotibial Band Autograft - Taoran Jin, M.D.; Jin Zhang, M.D. (Arthroscopy Techniques)
The labrum and capsule are indispensable structures for stability and the prevention of arthritis in the hip. Subsequent revision has been performed on patients who went through the failure of previous hip arthroscopic surgery, which caused the defect of the labrum and capsule, leading to continued hip pain and dysfunction postoperatively. For a select few patients, the labrum’s rerupture is beyond the scope of conventional suturing techniques, necessitating a reconstructive procedure to re-establish its integrity. Additionally, an attempt at secondary closure of the capsule can be challenging because of capsular limb adherence to the surrounding soft tissues. We describe a technique for simultaneous arthroscopic labral and anterior hip joint capsule reconstruction using an iliotibial band autograft. This procedure allows simultaneous reconstruction of the hip labrum and capsule stability with minimally invasive approaches to revise and re-establish the structural stability of the hip joint.